Hematomas orbitários post mortem. - D N Vieira; J Neto Murta; M C Cortesão; R Silva (Acta Médica Portuguesa, 1993)
Several cases of post mortem hematoma resulting from harvesting of the eye globes for transplantation, and susceptible of being misinterpreted as representing ante mortem trauma, are presented. Based on these cases the authors make a few considerations about the mechanisms of their production and technical procedures to avoid them.